Penerapan Etika Bisnis Syariah dalam Kinerja Pelaku UMKM pada Sektor Perdagangan - Ferdinand, Novingky; Kumala, Destiana; Hasan, Sawqi Saad El; Utarindasari, Destiana; Herawati, Ermi; Usman, Usman (Jurnal Manajemen Bisnis dan Keuangan, 2023)
Business ethics is responsible for determining the moral standards and behavior expected of players in the business world. In the context of MSMEs, business ethics plays an important role in creating a fair and honest business environment that can increase consumer confidence in the products and services offered. The purpose of this study was to determine the application of sharia business ethics to the performance of MSME actors in the Trade Sector in Bogor Regency. The methods used are qualitative and quantitative methods. The results of this study are that Business Ethics has a very strong influence on MSME performance.